Study of Protein/creatinine Ratio in Preeclampsia as an Alternative to 24 Hours Urine Protein in Manipal Teaching Hospital of Nepal - Shrestha, Pravin (Birat Journal of Health Sciences, 2018)
Introduction: Hypertensive disorder in pregnancy complicates around 5 to 10% of all pregnancies. It is one of the leading causes of maternal and fetal morbidity and mortality. Measurement of protein excretion by 24 -hour urine protein collection is gold standard but as it is time consuming, an alternative method like random urine protein/creatinine ratio is required. Objectives: The aim of this study was to assess the diagnostic accuracy of urine protein/ creatinine ratio compared with 24-hour urine protein as an alternative method for evaluating proteinuria in preeclampsia. Methodology: Patients with preeclampsia after 20 weeks of gestation were included in the study. Random urine protein/ creatinine ratio and 24-hour urine for protein was collected and evaluated for proteinuria. Results were entered and analysis was done. Results: Fisher's exact test depicted a positive association between UPCR with 24-hour urine protein, p value being less than 0.05. The area under curve was calculated as 0.87 95% CI (0.74-1.01), which was statistically significant. At cut off point of 0.3, sensitivity was 100%, specificity 90%, positive and negative predictive value 97.2% and 100% respectively. Conclusion: Random urine protein/ creatinine ratio (>0.3) is a reliable indicator of proteinuria >300mg/day. It can be used as an alternative to 24-hour protein estimation. BJHS 2018;3(1)5 : 350-353